Species identity and combinations differ in their overall benefits to Astragalus adsurgens plants inoculated with single or multiple endophytic fungi under drought conditions - Zuo, Yi-Ling; Hu, Qian-Nan; Qin, Le; Liu, Jia-Qiang; He, Xue-Li (Frontiers in Plant Science, 2022)
Although desert plants often establish multiple simultaneous symbiotic associations with various endophytic fungi in their roots, most studies focus on single fungus inoculation. Therefore, combined inoculation of multiple fungi should be applied to simulate natural habitats with the presence of local microbiome. Here, a pot experiment was conducted to test for synergistic effects between three extremely arid habitat-adapted root endophytes (Alternaria chlamydospora, Sarocladium kiliense and Monosporascus sp.). For that, we compared the effects of single fungus versus combined fungi inoculation, on plant morphology and rhizospheric soil microhabitat of desert plant Astragalus adsurgens grown under drought and non-sterile soil conditions. The results indicated fungal inoculation mainly influenced root biomass of A. adsurgens, but had no effect on shoot biomass. Both single fungus and combined inoculation decreased plant height (7% ~ 17%), but increased stem branching numbers (13% ~ 34%). However, fungal inoculation influenced the root length and surface area depending on their species and combinations, with the greatest benefits occurred on S. kiliense inoculation alone and its co-inoculation with Monosporascus sp. (109% and 61%; 54% and 42%). Although A. chlamydospora and co-inoculations with S. kiliense and Monosporascus sp. also appeared to promote root growth, these inoculations resulted in obvious soil acidification. Despite no observed root growth promotion, Monosporascus sp. associated its combined inoculations maximally facilitated soil organic carbon accumulation. However, noticeably, the three species combined inoculation had no significant effects on root length, surface area and biomass, but promoted rhizospheric fungal diversity and abundance most, with Sordariomycetes was the dominant fungal group. This indicates the response of plant growth to fungal inoculation may be different from that of rhizospheric fungal community. Structural equation modeling also demonstrated that fungal inoculation significantly influenced the interactions among growth of A. adsurgens, soil factors and rhizospheric fungal groups. Our findings suggest that, based on species specific and combinatorial effects, endophytic fungi enhanced the plant root growth, altered soil nutrients and facilitated rhizospheric fungal community, possibly contributing to desert plant performance and ecological adaptability. These results will provide basis for evaluating the potential application of fungal inoculants for developing sustainable management for desert ecosystems.